Complementary food exposure and children’s early understanding of food words: the approaching eating through language (APPEAL) study - Shapiro, Allison L. B.; Lawless, Megan C.; Charlifue-Smith, Renee; Johnson, Susan L. (Frontiers in Nutrition, 2024)
Language skills, such as the ability to understand words (receptive language), develop during infancy and are built through interactions with the environment, including eating. Exposure to complementary foods also begins in infancy and may play a significant role in language development, especially in understanding of food-related words. However, the relationship between the complementary foods to which a child is exposed and early language acquisition has not been previously studied. We hypothesized that young children's food-related receptive language (FRL) would reflect the complementary foods to which they were frequently offered by caregivers. Caregivers of young children (4-26 months; n=408) in the Approaching Eating through Language (APPEAL) Study in the US were surveyed via Qualtrics. FRL was assessed by caregiver-report via a modified MacArthur-Bates Communicative Development Inventory.Complementary foods offered (CFO) by caregivers were assessed using a modified Food Frequency Questionnaire. Latent Class Analysis (LCA) was implemented to identify, 1) groupings of foods frequently offered (>1x/week) and 2) groupings of food-related words understood by the young children. A 5-class best fit LCA model was identified for CFO (-log likelihood [-llik]=-8727) and for FRL (-llik=-5476). Cross-classification of the CFO and FRL derived classes revealed that children with higher exposure to complementary foods were perceived by caregivers to be most likely to also understand a greater number of food-related words (Probability=0.48). As expected, children having been offered a greater number of complementary foods and who understood a greater number of food-related words were older, compared to those with less complementary food exposure and food-related language acquisition (p<0.001). These findings support the potential role of introduction to complementary foods in development of food-related language.